2007
DOI: 10.1359/jbmr.061009
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Phosphate Intake Reduces Bone Strength in the Growing Rat Skeleton

Abstract: Nutrition influences peak bone mass development in early adulthood. The effect of high dietary phosphate intake on the growing skeleton of 1-month-old male rats (n = 30) was assessed in an 8-week intervention. High dietary phosphate intake increased bone remodeling and impaired bone material properties, diminishing bone mechanical strength.Introduction: High dietary phosphate intake is typical in the Western diet. Abundant phosphate intake enhances parathyroid secretion and bone metabolism. To study the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…It has been suggested that a high-P diet contributes to bone loss in humans as well as animals (3)(4)(5). In the present study, a high-P diet decreased serum Ca concentrations and increased serum P concentrations, which caused an increase in serum PTH concentration.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It has been suggested that a high-P diet contributes to bone loss in humans as well as animals (3)(4)(5). In the present study, a high-P diet decreased serum Ca concentrations and increased serum P concentrations, which caused an increase in serum PTH concentration.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, food intake and final body weight were lower in rats fed the high-P diet compared with those fed the control diet. Previous studies have also shown that a high-P diet decreases food intake (4,5). Therefore, it is thought that the decreased food intake and body weight associated with a high-P diet influence bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the respective calcium contents of femurs, mandibles, and lumbar vertebrae were significantly decreased . High phosphate (1.2% and 1.8%) intake limits bone growth and increases the number of osteoclasts, and also reduces bone stiffness and toughness in the femoral neck and tibial shaft (Huttunen et al, 2007).…”
Section: Influence Of Pi On Bone Resorption In Animalsmentioning
confidence: 99%
“…1 Recent epidemiologic and experimental studies have further amplified the role this condition plays in the larger story of CKD-MBD. Experimental studies have demonstrated that high phosphorus plays a key role in the development of vascular calcification 2 and impairment of bone mass and strength, induces changes in the expression pattern of muscle and bone-related genes, 3,4 and may also act as a pro-aging factor. 5 In addition, clinical studies have demonstrated an association among hyperphosphatemia, vascular stiffness, and left ventricular hypertrophy.…”
mentioning
confidence: 99%